IMPACT OF HEDONISTIC TRUST AND VALUE ON DIGITAL WALLET USER LOYALTY IN INDONESIA THROUGH SATISFACTION MEDIATOR - Pradipta Utama, Andyan; Nana Trisnawati; Fitri Nurulafiah; Widiastuti Alawiah (Dinasti International Journal of Digital Business Management, 2022)
The Covid-19 pandemic made people have to avoid physical contact, this provides a promising opportunity in the era of industrial revolution 4.0, particularly in the financial industry and e-commerce business. The physical distancing policy pushed by the World Health Organization (WHO) has motivated people to engage in contactless activities, one of which is payment transaction. Government authorities in some countries are taking action to encourage non-contact payments as a precaution against the growing spread of the virus. People are worried that Covid-19 can be contracted through physical money, prompting them to shift to digital platforms (e-wallets). The background of this research is the phenomenon of the growing application of digital wallets as a payment medium that is currently a necessity for the community. Loyalty is a crucial aspect in the financial industry to continue to strive in competitive business climate. Many factors that affect customer loyalty, especially in financial services of digital wallet platform providers, such as trust, hedonic value, and customer satisfaction, are suspected of playing a role in the loyalty of digital wallet users. On the basis of the above phenomenon, the objective of this study is to analyze the role of satisfaction as a mediator for the impact of trust and hedonic value on the loyalty of digital wallet users. The population of this study is digital wallet users located in DKI Jakarta, with a sample number is 302 people. Data analysis methods use the Structural Equation Model (SEM).